CROSST - Version 1.0.1 - Mukiri, Jessica; Diogo, Rodrigue V. Cao; Gbedjissokpa, Sènami G.M.; Kinyua, Michael; Hoek, Rein van der; Paul, Birthe K.; Sommer, Rolf (International Center for Tropical Agriculture, 2019)
CROSST is an Excel-based tool that assesses both agro-environmental and socio-economic impacts of Green Manure Cover Crop (GMCC) technologies. The tool quantifies gross economic margin, productivity (yield), soil health (N and P balances, soil structure, and soil organic carbon), required labor hours, and the trade-offs between these indicators. The tool was pilot-tested in Benin and Kenya under the BMZ-GIZ program on ‘Soil Protection and Rehabilitation for Food Security.’